Reimagining belonging: The quest of Africans for relational belonging and the Australian requirement of integration - Woldeyes, Yirga Gelaw (University of Barcelona, 2018)
This paper reflects on the challenges African refugees face in achieving a sense of belonging in Australia, largely as a result of the negation of their traditional experiences by modernist states both in Africa and Australia. In Australia, the dream of belonging to a new community is constrained by what I call the ethnicisation of civic belonging, a process whereby legal frameworks around residency and citizenship become beholden to the Eurocentric interpretation of ‘Australian values.’ This can be seen in citizenship exams that test a refugee’s adherence to such values, and often results in broader social pressure to assimilate in order to belong. The paper seeks to challenge and reimagine current attempts to integrate African refugees into Australian society by considering African notions of belonging, using the importance of personhood and relationship with nature as important examples. The paper then considers how state violence towards communal belonging in Africa contributes to displacement and the quest for belonging to a new community. African refugees have lost their physical belonging which constituted their relationship to land, ancestors and communities, and are in search of reconstituting belonging in new places. The paper argues that refugees will continue to live in a constant struggle to achieve belonging unless they are seen not simply as vulnerable beings who seek protection but also as active agents who bring new perspectives that enrich diverse ways of being and belonging to Australia.